Effects of the knockdown of hypoxia inducible factor-1α expression by adenovirus-mediated shRNA on angiogenesis and tumor growth in hepatocellular carcinoma cell lines - Choi, Sung Hoon (The Korean Association for the Study of the Liver, 2010)
BACKGROUND/AIMS: Hypoxia-inducible factor-1α (HIF-1α) is a central transcriptional factor involved in the cellular responses related to various aspects of cancer biology, including proliferation, survival, and angiogenesis, and the metabolism of the extracellular matrix in hypoxia. This study evaluated whether adenovirus-mediated small hairpin RNA (shRNA) against HIF-1α (shHIF-1α) inhibits cell proliferation and angiogenesis in hepatocellular carcinoma (HCC) cell lines. METHODS: Knockdown of HIF-1α expression was constructed by adenovirus-mediated RNA interference tools, and HCC cell lines infected with shHIF-1α coding virus were cultured under a hypoxia condition (1% O(2)) for 24 hours. Following infection, the expression levels of HIF-1α, angiogenesis factors, and matrix metalloproteinase (MMP) were examined using Western blotting. Cell proliferation and angiogenesis were measured by a cell proliferation assay (MTT assay) and an angiogenesis-related assay (invasion and tube-formation assay), respectively. RESULTS: Adenovirus mediated inhibition of HIF-1α induced suppression of tumor growth in HCC cell lines. It also down-regulated the expression of angiogenesis factor and MMP proteins. Angiogenesis as well as mobility of vascular cells to tumor was suppressed by adenovirus-mediated shHIF-1α-infected groups in human umbilical vein endothelial cells (HUVECs). CONCLUSIONS: These data suggest that adenovirus-mediated inhibition of HIF-1α inhibits the invasion, tube formation, and cell growth in HUVECs and HCC cells.